(untitled) (Journal of Parents and Teachers, 2014)
Contemporary art is a movement loaded with prejudices, as it is common to hear comments such as "This is incomprehensible" or "Anyone can do this". This is why the CGAC (Centro Galego de arte Conteporánea) tries to alleviate this situation by offering talks with students in the classrooms of the centres. Through these talks, they deal with current issues with secondary school students, such as Displaced, emigrants and exiles; Transgression, authority and art; Nature and Ecology; and the recently added Women and society; Visual culture; New technologies, Art and activism; Ways of looking. These talks propose an approach to contemporary art by bringing young people closer to today’s culture by proposing topics of interest and debate.